Correlation between Non-communicable Diseases and Curcumin Use - S, Viswa; A, Roshny; B, Naveen Kumar; Babu, Linsha; S, Anandhaseyanam; N, Senthil Kumar (Journal of Pharmacy Practice and Community Medicine)
Background: Non-communicable Diseases (NCDs) are increasing rapidly all over the world, on the other hand, curcumin has various medicinal properties against NCDs and it is a major ingredient in our household/recipes. So why can’t we study such an important natural herb in preventing and treating various chronic diseases. Another important factor for the selection of this study was the outbreak of COVID-19 and people had increased awareness about turmeric/curcumin use during this pandemic situation. Objectives: To find out the prevalence of non-communicable diseases across various centers and correlate with the usage of curcumin in these centers and also to understand the global scenario of how curcumin is better utilized and what its position in India. Materials and Methods: A descriptive cross-sectional study was performed in Erode, Komarapalayam, Kallakurichi, Nagapattinam situated in the state of Tamil Nadu, India for a duration of 6 months. A simple random sampling method was adopted to choose the households and then a self-structured questionnaire has been given to collect the details like demographic and disease status with turmeric use and their awareness status. The Mann-Whitney U test was used to compare curcumin use related to non-communicable diseases. The p-value of <0.05 was considered as significant. Results: A total of 1276 households were included with 4495 family members; the majority of participants were female (99.7%). Among the population, the prevalence of non-communicable diseases is cardiovascular diseases (7.7%) followed by diabetes (7.6%), arthritis (3.6%), asthma (0.9%), cancer (0.1%), Alzheimer’s disease (0.2), psoriasis (0.5%) and others (1.5%) include hypothyroidism, ulcer, and neuropsychiatric disorders. The average years of turmeric use (42.8 years) among the households and the average amount (1.8 g) of curcumin in their daily recipes were found along with the average daily curcumin use of 0.54 g. By applying the Mann-Whitney U test, there was a significant association between diabetes and arthritis with curcumin use was verified. Conclusion: The present study highlights that the prevalence of diabetes and arthritis was significantly associated with curcumin use. On the other side, people in India were more aware of curcumin as a medicinal herb and consumed higher amounts particularly during the COVID-19 pandemic.
Keywords: Curcumin; Non-communicable Disease; Diabetes; Arthritis; Correlation